Analysis of Front Office Management Information System at RYD Family Hotel Cikoneng - Maulana, Soni Farid; Sutarsa, Monika (PT. Riset Press International, 2025)
Collecting hotel front office administrative data requires appropriate mechanisms and organizational arrangements so that the data can be packaged and maintained properly. As one of the modern hotels in Ciamis city center, RYD Family Hotel is a hotel that is currently under development. Currently, the RYD Family room rental system is still less effective in terms of reservation retention, delays in finding empty rooms, frequent delays in reporting, and the length of time to calculate check-out fees. Therefore, to be more effective, the author aims to create an efficient and effective front office information system. Therefore, the benefits obtained through this computerized system are expected to provide convenience in processing front office check-in and check-out customer data, ease in storing customer data, viewing customer data reports, income reports, daily, monthly and period reports. Using research methods, the author analyzes existing data sources to create a system, designs input and output based on this analysis, and creates tables and program code to become the desired system.